As árvores como narrativa para a relação humana com o tempo e o espaço - Würker, Helena (2023)
The research deals with the relationship between human beings and nature, especially with trees, with the objective of contributing to a broader and more critical perception of the human relationship with time and space as a curricular element. The matter of social distancing imposed by the pandemic generated by COVID 19, in 2020, constitutes the basis for our research problem, when the encounters were suspended in the school space, causing the rupture of spacetime, generating disintegration of experiences and curricular experiences. The pedagogical foundation used was the Waldorf Pedagogy, which has the curriculum from a perspective of daily construction of knowledge, with the observer in a phenomenological study, composing a relationship between the development of humanity and human development. The theoretical basis of the research is composed of the contributions of Rudolf Steiner, Johann Wolfgang von Goethe, Maurice Merleau-Ponty, Paulo Freire, Paul Ricoeur, Byung-Chui Han, among others, which refer to the reading of the phenomenological path that enables actions for otherness in search of a more liberating and active education in the world, in which its construction is done in the relationship with the other and with nature. The methodological approach is qualitative, based on empirical, documentary and active participation research, using the following techniques: analysis of documents and records of students aged 8 years, one of the learning milestones of time, and by observation and recording in field diary. This work, as a contribution to the curriculum, is expected to enlarge the reflection on the relationship of human beings with time and space, through a (re)appropriation of experiences and experiences of bonds with trees